Dietary adequacy and nutritional status of Meitei community of Manipur, Northeast India - Loukrakpam, Bidyalakshmi (Matern Child Nutr, 2020)
Meitei is the main ethnic community that belongs to the north‐eastern state of Manipur in India. This community is bestowed with rich biodiverse resources with indigenous foods still form an integral part of their diet. However, limited data on the food and nutrient consumption as well as nutritional status of this community are available. This study was carried out on the children, adolescents and women of reproductive age (WRA) of this community from 12 villages, to determine their food consumption pattern and nutritional status. Basic anthropometry and 24‐h dietary intake assessment was conducted. The prevalence of underweight was 27%, stunting was 45% and wasting was 12% in children below 5 years. Stunting was observed among 34% of children 5–17 years of age. About 7% of WRA were undernourished, while 28% were overweight or obese. About 55% of 1–7 year‐old children had mean probability adequacy of 12 micronutrients <0.5, and the adequacy of individual micronutrients namely vitamin A, E and calcium were low. Dietary determinants such as low dietary diversity score, dietary species richness and the lowest tertiles of different food groups' intake (except for sugars, fish and sea foods and spices and condiments) predicted micronutrient inadequacy. In addition to a high prevalence of undernutrition in children and adolescents and overnutrition in WRA, the effect of various dietary determinants on micronutrient adequacy in the study group of the Meitei community are reported.